Novel and emerging targets for cholangiocarcinoma progression: therapeutic implications. (2nd January 2022) - Kankeu Fonkoua, Lionel A.; Serrano Uson Junior, Pedro Luiz; Mody, Kabir; Mahipal, Amit; Borad, Mitesh J.; Roberts, Lewis R.
ABSTRACT: Introduction: Cholangiocarcinoma (CCA) is a heterogeneous group of aggressive biliary malignancies. While surgery and liver transplantation are the only potentially curative modalities for early-stage disease, limited options are available for most patients with incurable-stage disease. Survival outcomes remain dismal. Recent molecular profiling efforts have led to improved understanding of the genomic landscape of CCA and to the identification of subgroups with distinct diagnostic, prognostic, and therapeutic implications. Areas covered: : We provide an updated review and future perspectives on features of cholangiocarcinogenesis that can be translated into therapeutic biomarkers and targets. We highlight the critical studies that have established current systemic chemotherapy and targeted therapeutics, while elaborating on novel targeted and immunotherapeutic approaches in development. Relevant literature and clinical studies were identified by searching PubMed and www.ClinicalTrials.gov . Expert Opinion: : While therapies targeting the various molecular subgroups of CCA are rapidly emerging and changing treatment paradigms, their success has been limited by the genetic heterogeneity of CCA and the plasticity of the targets. Novel strategies aiming to combine immunotherapy, chemotherapy, and molecularly targeted therapeutics will be required to offer durable clinical benefit and maximize survival.